Identification of assets and statement of wireless technologies to support real time location systems: case RNEST - Abreu e Lima refinery. (2016) - Cruz, Larissa P.M.; Landau, Luiz; Cunha, Gerson Gomes; Lopes, Maria Celia S.
This study aims to present a methodology that helps to choose the most appropriate technology for asset tracking in harsh environments, as well as make possible a more assertive identification of assets to be tracked. The method used is the correlation between metric parameters of performance and the technical characteristics of sensors that are based on the real-time location systems (RTLS) as: infrared, ultrasound, Bluetooth, UWB, RFID, Zigbee and GPS. Thus, you get a table with qualitative indicators that are subsequently aligned in ascending order of operation, generating chart radar to view clearly this evaluative rating. This method was applied to a tracking case in a harsh environment as the Abreu e Lima Refinery - RNEST. The development of this method and its application aims to minimise planning and deployment errors, enabling the development of RTLS's systems with more appropriate technologies.